The Changing Nature of the Graduate Labour Market: Media, Policy and Political Discourses in the UK - Tholen, Gerbrand; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The assumptions made in the media regarding graduate skills and occupations are no longer valid within the changing educational context. This book traces seven key trends that shape the graduate labour market and reveals that their effects contradict the conceptualisation of the graduate labour market which dominates media and policy discourses.
Keywords: Science; Science; Science, general